Bentuk Partisipasi Masyarakat dalam Pengembangan Kampung Herbal Nginden Kecamatan Sukolilo Surabaya - Triatmojo, Daniel Wahyu; Arizar, Lucky; Kinasih, Naba Arum; Mazidah, Rahma Rizqiyatul; Prathama, Ananta (IAI Nasional Laa Roiba Bogor, 2024)
This research is motivated by a condition where unused government-owned land is managed by the community and is then transformed into productive land and a better environment. Therefore, the aim of this research is to determine the forms of participation provided by the residents of Nginden RT 9 RW 5 to develop the Nginden Herbal Village program sustainably. This research uses a qualitative method with a case study approach. Research data collection uses primary data sources such as interviews, observations, and documentation as well as secondary data sources like news articles, books, previous research results, and other sources relevant to the research. The data analysis technique used in this research is the interactive model from Miles and Huberman. In comparison, triangulation is used to appropriately process the collected data. The results of the research show that the community of Nginden Herbal Village participates well. This can be seen from the theory of community participation according to Huraerah: the form of thought participation, the form of property participation, the form of skill and proficiency participation, and the form of social participation have been well implemented. In addition, the form of labor participation has been quite well implemented. The community has made many efforts to realize the common goal of improving the welfare of the surrounding environment. Therefore, this effort needs support and attention from the government and always requires the role of the community itself to continue managing it so that an already good environment becomes even better.